Photosynthesis Regulation in Response to Fluctuating Light in the Secondary Endosymbiont Alga Nannochloropsis gaditana. (12th September 2019) - Bellan, Alessandra; Bucci, Francesca; Perin, Giorgio; Alboresi, Alessandro; Morosinotto, Tomas
Abstract: In nature, photosynthetic organisms are exposed to highly dynamic environmental conditions where the excitation energy and electron flow in the photosynthetic apparatus need to be continuously modulated. Fluctuations in incident light are particularly challenging because they drive oversaturation of photosynthesis with consequent oxidative stress and photoinhibition. Plants and algae have evolved several mechanisms to modulate their photosynthetic machinery to cope with light dynamics, such as thermal dissipation of excited chlorophyll states (non-photochemical quenching, NPQ) and regulation of electron transport. The regulatory mechanisms involved in the response to light dynamics have adapted during evolution, and exploring biodiversity is a valuable strategy for expanding our understanding of their biological roles. In this work, we investigated the response to fluctuating light in Nannochloropsis gaditana, a eukaryotic microalga of the phylum Heterokonta originating from a secondary endosymbiotic event. Nannochloropsis gaditana is negatively affected by light fluctuations, leading to large reductions in growth and photosynthetic electron transport. Exposure to light fluctuations specifically damages photosystem I, likely because of the ineffective regulation of electron transport in this species. The role of NPQ, also assessed using a mutant strain specifically depleted of this response, was instead found to be minor, especially in responding to the fastest light fluctuations.